Guided “LegislEUlab” on the Drafting of Multilingual Legal Provisions in the EU: Concept of the Cologne Summer School for European Legal Linguistics - Dillmann, Ruben; Mattissen, Johanna (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
Legal training at German universities does not cover the practicalities and challenges of lawmaking. The innovative concept of the Cologne Summer School for European Legal Linguistics “LegislEUlab” encompasses the transdisciplinary teaching, simulation and analysis of the EU legislative procedure. The participants are students of law and translation from various EU Member States. In mixed teams, they prepare their own drafts, implementing the materials of a current proposal for an EU legislative act. They develop an awareness and deeper understanding of linguistic structure, multilingual drafting and its legal effects, comprehensibility of legal provisions and their interpretation and application.
Keywords: European Legal Linguistics; Cologne Summer School; lawmaking; simulation; transdisciplinary approach; LegislEUlab; legal training; translation